Toxicology of the immune system - Burns Naas, Leigh Ann (Henry Stewart Talks, 2011)
Introduction to the Immune System, Assessment of Immunocompetence, The Immune System in Regulatory Toxicology Testing, including ICH S8: Adverse (Unintended) Immunomodulation, Immune-Mediated Disease, Risk Evaluation